Efektifitas Terapi Massage Terhadap Cedera Olahraga Nyeri Tumit Dan Nyeri Otot Tibialis Pada Atlet Futsal SMPN 18 Kota Bengkulu - Dibyo ika pratama; Sugiyanto Sugiyanto; Santun Sihombing (Universitas Bengkulu, 2020)
In futsal, there will often be body contact and injury prone. Futsal is a high-intensity sport that is characterized by the activity of running repeatedly with a relatively long time so that the risk of injury to the feet. Heel pain and tibial muscle pain are common in futsal players. The purpose of this study was to determine: a) the effectiveness of massage therapy for heel pain sports injuries in futsal athletes of SMPN 18 Bengkulu City and b) the effectiveness of massage therapy for tibial muscle pain sports injuries in futsal athletes of SMPN 18 Bengkulu City. This research is a field research with a qualitative approach. The data source in this study is the physical education teacher and all futsal athletes of SMPN 18 Bengkulu City who suffer from sports injuries of heel pain and tibial muscle pain. The technique of collecting data is done through interviews, observation and documentation. The data obtained were analyzed using Creswell's theory (2014). The results showed that massage therapy was very effective against sports injuries of heel pain and tibial muscle pain in futsal athletes of SMPN 18 Bengkulu City.